The use of functionally graded dental crowns to improve biocompatibility: a finite element analysis. Issue 2 (25th January 2018) - Mahmoudi, Mojtaba; Saidi, Ali Reza; Hashemipour, Maryam Alsadat; Amini, Parviz
Abstract: In post-core crown restorations, the significant mismatch between stiffness of artificial crowns and dental tissues leads to stress concentration at the interfaces. The aim of the present study was to reduce the destructive stresses by using a class of inhomogeneous materials called functionally graded materials (FGMs). For the purpose of the study, a 3-dimentional computer model of a premolar tooth and its surrounding tissues were generated. A post-core crown restoration with various crown materials, homogenous and FGM materials, were simulated and analyzed by finite element method. Finite element and statistical analysis showed that, in case of oblique loading, a significant difference ( p  < 0.05) was found at the maximum von Mises stresses of the crown margin between FGM and homogeneous crowns. The maximum von Mises stresses of the crown margin generated by FGM crowns were lower than those generated by homogenous crowns (70.8 vs. 46.3 MPa) and alumina crown resulted in the highest von Mises stress at the crown margin (77.7 MPa). Crown materials of high modulus of elasticity produced high stresses at the cervical region. FGM crowns may reduce the stress concentration at the cervical margins and consequently reduce the possibility of fracture.